Human papillomavirus and Chinese international students in the United States: attitudes, knowledge, vaccination trends, healthcare behaviors, and sexual activity. Issue 1 (31st December 2022) - Esagoff, Aaron; Cohen, Samuel A.; Chang, Guoxuan; Equils, Ozlem; Van Orman, Sarah
ABSTRACT: Human papillomavirus (HPV) is the most common sexually transmitted infection in the world, with the ability to cause external genital warts and cancers. The HPV vaccine, first released in the United States of America (USA) in 2006, has been shown to protect against the highest risk HPV strains responsible for the majority of HPV-related cancers. In mainland China, the HPV vaccine was only recently approved in 2016 and is therefore not readily available. As a result, Chinese international students (CIS) studying in the USA continue to have low HPV vaccination rates. This study completed in person and online surveying of 396 CIS at a large Southern California university, with the goal of better understanding CIS knowledge and awareness of HPV disease, vaccination and healthcare behaviors, and sexual activity. Among participants, the reported HPV vaccination rate was 61% (females: 85%; males: 32%). HPV vaccination was significantly correlated with a past visit to the on-campus student health center, having university-sponsored student health insurance, higher self-perceived HPV knowledge, and increased willingness to pay for vaccination. A large portion of participants portrayed low levels of sexual activity, which suggests that CIS can take advantage of catch-up HPV vaccination recommendations through 26 years of age. The results of this study can be used to inform policy initiatives, particularly at the campus level, that attempt to improve HPV vaccination rates amongst CIS.